2016
DOI: 10.1002/app.43298
|View full text |Cite
|
Sign up to set email alerts
|

Ductile tear behavior of multilayered polypropylene homopolymer/ethylene 1‐octene copolymer sheets

Abstract: The tear resistance of the polypropylene homopolymer (HPP)/ethylene 1-octene copolymer (POE) alternating multilayered sheets, which were prepared through multilayered coextrusion, was evaluated. Polarized optical microscope (POM) photographs revealed that HPP and POE layers aligned alternately vertical to the interfaces and continuously parallel to the extrusion direction. Tear results demonstrated the conventional blends had less tear-resistant than the multilayered samples. Large plastic deformation of HPP l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It can be attributed to the fact that intense extensional stress can form the IMN structure and induce the formation of thicker lamellae (see SAXS and WAXD results), promoting a pronounced increase of the maximum piercing force . Furthermore, the excellent toughness of films can stabilize the crack growth and consume large amounts of energy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be attributed to the fact that intense extensional stress can form the IMN structure and induce the formation of thicker lamellae (see SAXS and WAXD results), promoting a pronounced increase of the maximum piercing force . Furthermore, the excellent toughness of films can stabilize the crack growth and consume large amounts of energy …”
Section: Resultsmentioning
confidence: 99%
“…52 Furthermore, the excellent toughness of films can stabilize the crack growth and consume large amounts of energy. 53 Based on the findings, the specific mechanism is proposed to shed light on the formation of IMN and the improvement of integrated performance, illustrated in Figure 8. As shown in Figure 8a, the cocontinuous structure can evolve into IMN via "casting−thermal stretching".…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The tear behavior of multilayered sheets, consisting of alternating PP and EOC layers, has also been investigated. He et al (2016) observed, for a PP/EOC multilayer film, that both the tear strength and energy are higher than those of the corresponding conventional blend.…”
Section: Introductionmentioning
confidence: 87%
“…These structures make POE have better mechanical strength and weather resistance, while the cost is also reduced. 9 Considering the application field of this material, it is necessary to study its flame retardant modification. Deng et al 10 used modified ammonium polyphosphate (MAPP) to modify POE / PE thermoplastic elastomer.…”
Section: Introductionmentioning
confidence: 99%